The realignment of Pennsylvania politics since 1960 : two-party competition in a battleground state - Lamis, Renée M. (Pennsylvania State University Press, 2009)
"Explores electoral changes in Pennsylvania since 1960, finding that the recent "culture-wars realignment" has significantly altered the old New Deal party system, especially since the early 1990s. Contains illustrations plotting political alignment of Pennsylvania counties"--Provided by publisher